(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2023)
This paper aims to analyze the ecological problems that Brazil is currently facing, namely deforestation. It delves into the leading industries that contribute to deforestation, its local and global ramifications, and some potential solutions. The paper concludes by describing how Brazil’s current political transition will affect policies to halt deforestation. For additional context, listen to the author’s reflection on the piece below.